2020
DOI: 10.1097/md.0000000000019463
|View full text |Cite
|
Sign up to set email alerts
|

Primary testicular diffuse large B-cell lymphoma

Abstract: Rationale: Primary testicular lymphoma (PTL) is a rare type of extranodal non-Hodgkin's lymphoma (NHL). Although data of PTL in patients with diffuse large B-cell lymphoma (DLBCL) are accumulating, there are still patients respond poorly to prognosis. Patient concerns: All patients had disease of the DLBCL subtype and those patients had primary involvement of the testis. In our studies, eleven patients had stage I/II disease, and 3 patients had advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
1
20
0
1
Order By: Relevance
“…A recent study by Wang et al [6] included 16 patients with primary testicular-DLBCL. The median age of the patients was 62 years (range, 36–93 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Wang et al [6] included 16 patients with primary testicular-DLBCL. The median age of the patients was 62 years (range, 36–93 years).…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by our data: 12 patients (80%) presented with testicular swelling. Furthermore, Wang et al [6] showed that 11 of 16 patients had stage I or II disease and 3 of 16 had advanced disease with systemic symptoms. In contrast, 2 patients (13.33%) in our series had systemic symptoms, and 10 patients (66.67%) had advanced disease (Ann Arbor stage IVE).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular lymphoma is about 5 % of testis malignancies. Primary forms are usually “diffuse large B cell”, a high-grade histotype; metastatic ones often show Burkitt cells [8] . Herein, it was a primary TBL.…”
Section: Discussionmentioning
confidence: 99%
“…(20,21) La terapia multimodal consta de, la orquiectomía radical (diagnóstica terapéutica) seguida de quimioterapia R-CHOP (rituximab, ciclofosfamida, doxorubicina, vincristina y prednisona), radioterapia local (profiláctico para prevenir la recaída en ganglios linfáticos regionales o en los testículos contralaterales) y profilaxis del SNC con dosis altas de metotrexato con o sin quimioterapia intratecal, son opciones ampliamente aceptadas, que son adecuadas para uso clínico individual con niveles de evidencia de tipo 3. (21) El rituximab es un anticuerpo monoclonal quimérico anti-CD20 de inmunoglobulina humana G aprobado para el tratamiento del linfoma folicular recurrente. (22) La mayoría de las recaídas ocurren dentro de los primeros 1-3 años de la terapia inicial, principalmente en los sitios extra-nodales.…”
Section: Discussionunclassified